LUMINESCENCE STUDIES ON INTRAZEOLITIC MIGRATION OF TB(III) PENS BY THERMAL TREATMENTS .2. LTA-TYPE ZEOLITES - HONG, SB; SHIN, EW; MOON, SH; PYUN, CH; KIM, CH; UH, YS (AMER CHEMICAL SOC, 1995)
Analysis of the luminescence spectra obtained from TbNa-LTA zeolites with different framework Si/Al ratios treated as a function of temperature reveals that the Tb(III) ions located at site S5 in supercages migrate ineversibly to site S2' in sodalite cages by heating at 373 K. In particular, the cations in LTA zeolites with Si/Al ratios higher than unity are rearranged inside the sodalite cages when treated at temperatures higher than 573 K. This can be qualitatively correlated to differences in local environment of Tb(III) ion sites in sodalite cages.
Keywords: ION-EXCHANGED-ZEOLITE; A-ZEOLITE; SPECTROSCOPY; FAUJASITE; SILICON